Conferências de saúde enquanto instrumento de participação no SUS - Medeiros, Katiusca Torres (2011)
The promulgation of the Federal Constitution in 1998 extended universally the right to health and, regulated by the Law No. 8080/90, the National Health System (SUS) took the responsibility of assisting the citizens according to their needs. The institution of this new conception of health has also brought a new nature to the assistance practices. Health as a social right involves not only care, prevention, and promotion of health but also the social participation and control of all the mechanisms of the Health Policy, a characteristic that has influenced other policies in Brazil. These achievements are fruits of the fight for the Health Sector Reform. Such fight had its culmination in the VIII National Health Conference, which had many of its proposals absorbed into the Constitution of 1998, changing the structure of health policy in Brazil to a more democratic model that deals with the participation of the society in managing the health system, thereby beginning a new era to the health policy in Brazil. In this way, this study aimed to analyze whether the proposals of the health conferences in national, state, and local level - taking the state of Paraíba and the city of João Pessoa as a basis have been strengthening the exercise of social control. This study used a critical dialectical approach, whose methodology was the analysis of documents and literature regarding to those conferences. We have found that there are several mechanisms to fight for the consolidation of social control, but there are also several mechanisms deconstructing the exercise of democracy and rights. These deconstructing mechanisms, through destructuring forms of health councils and other bodies, directly affect the implementation of social control in Brazil. There is still much to do in the pursuit of ensuring a greater solidity of the social control, and this pursuit passes directly through education from basic to the highest levels of education in order to form citizens who understand and are committed to the health system, social control, and their rights.